Morphology of healthy leaves and galling leaves in Pistacia terebinthus L. - Louzabi S.; Belhadj S.; Bouragba Brague N. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The pistachio is one of the genetic resources under threat of extinction in Algeria, given the combination of stresses of biotic and abiotic nature. Among these biotic factors, the aphids can induce galls on the leaves and hence, change their morphology. The study of morphological changes occurred on the leaves of Pistacia terebinthus, L. following gall aphids attack was analyzed in two different sites in the province of Djelfa (Gottiya and Senalba) in Algeria. Ten healthy leaves and ten galling leaves were sampled from ten trees of P. terebinthus. Quantitative analysis of morphological variables of healthy and infected leaves has been conducted. T-test showed highly significant differences between infected and healthy leaves of P. terebinthus regarding the length, the width of the leaves, the terminal leaflet and the petiole length.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)